Effect of Heart rate on Basketball Three-Point Shot Accuracy - Ardigò, Luca P.; Kuvacic, Goran; Iacono, Antonio D.; Dascanio, Giacomo; Padulo, Johnny (Frontiers in Physiology, 2018)
The three-point shot (3S) is a fundamental basketball skill used frequently during a game, and is often a main determinant of the final result. The aim of the study was to investigate the effect of different metabolic conditions, in terms of heart rates, on 3S accuracy (3S%) in 24 male (Under 17) basketball players (age 16.3±0.6 yrs). 3S performance was specifically investigated at different heart rates. All sessions consisted of 10 consecutive 3Ss from five different significant field spots just beyond the FIBA three-point line, i.e., about 7 m from the basket (two counter-clockwise “laps”) at different heart rates: rest (0HR), after warm-up (50%HRMAX [50HR]), and heart rate corresponding to 80% of its maximum value (80%HRMAX [80HR]). We found that 50HR does not significantly decrease 3S% (-15%, P=0.255), while 80HR significantly does when compared to 0HR (-28%, P=0.007). Given that 50HR does not decrease 3S% compared to 0HR, we believe that no preliminary warm-up is needed before entering a game in order to specifically achieve a high 3S%. Furthermore, 3S training should be performed in conditions of moderate-to-high fatigued state so that a high 3S% can be maintained during game-play.